An analysis of software-defined routing approach for wireless sensor networks. (November 2016) - Manisekaran, S.V.; Venkatesan, R.
Abstract: In emerging wireless sensor applications, sensor nodes are equipped with low battery and limited capacity when transmitting the sensed data to the sink.To prolong the lifetime of sensor networks, the energy consumption has to be reduced and the bandwidth channel utilization has to be improved. To accomplish these requirements, we have proposed a new scheme as software based multi-flow in wireless sensor network. This scheme is developed based on the Software Defined Network (SDN) and allocates separated channels for data plane and control plane. It also generates inbuilt software module in every sensor nodeto increase the speed of the network. The proposed scheme is used to maintain the topology and also manages the limited battery power usage. Experimental results demonstrate the performance of the proposed software based multi flow in terms of indispensible network parameters including throughput, delay and energy consumption.